The resource curse phenomenon in the case of precious metals: A panel evidence from top 19 exporting countries - Ozcan, Burcu; Temiz, Mehmet; Tarla, Esma Gueltekin (Elsevier Sci Ltd, 2023)
The theory suggests that a resource curse is more likely for precious products (such as gold, diamond, and silver) than agricultural products. Therefore, based on this theoretical claim, this study aims to analyze the resource curse hypothesis for a panel of the top 19 exporting countries of precious metal ores and concentrates. Based on different panel data models and annual data from 2001 to 2021, we confirm the presence of a resource curse. In addition to labor and capital variables, the model is extended with institutional quality and human capital variables. By doing so, the direct and indirect impacts of institutional quality and human capital on economic growth are analyzed. The results reveal that both variables significantly and positively impact economic growth. In contrast, their indirect impacts are insufficient to reverse the resource curse into a blessing. Finally, some important policy implications are suggested based on the empirical findings, such as the sustainable utilization and management of natural resources and their rents, the regulation of education policies to increase the national human capital stock, and the necessity of increasing the institutional quality level to prevent corruption and rent-seeking behaviors.
Keywords: Resource curse; Natural resource rents; Institutional quality; Human capital; Panel data model